Development of the Ileal Microbiota in Three Broiler Breeds - Richards-Rios, Peter; Fothergill, Jo; Bernardeau, Marion; Wigley, Paul (Frontiers in Veterinary Science, 2020)
The development and succession of the microbiota in ileal mucus and lumen samples from three breeds of broiler chicken (Cobb 500, n = 36; Hubbard JA87, n = 38; and Ross 308, n = 36) was observed between 3 and 42 days post hatch (d.p.h). Chicks were housed in the same room of a climate-controlled, biosecure chicken housing unit. Between 0 and 14 d.p.h, chicks were kept in three circular brooder pens ensuring a mixture of breeds in each brooder. From 22 d.p.h, chicks were removed from the brooders and kept in the same room. DNA was extracted from a pooled sample of ileal mucus and luminal contents taken from five birds of each breed at 3, 7, 14, 21, 28 and 42 d.p.h. High-throughput Illumina sequencing was performed for the V4 hypervariable region of the 16S rRNA gene. The initial microbiota in the ileum varied between breeds. The common features were a low diversity and general dominance by one or two taxa such as Enterococcus or Escherichia with relatively low numbers of Lactobacillus. Escherichia became the most abundant genus in samples where Enterococcus was previously the dominant taxa. The next phase of development was marked by an increase in the abundance of Candidatus Arthromitus in the mucus and Lactobacillus in the lumen. The high abundance of Candidatus Arthromitus persisted between 7 and 14 d.p.h after which Lactobacillus became the most abundant genus in both the mucus and lumen. Dominance of the ileal microbiota by Lactobacillus was a transient feature. By 42 d.p.h, the relative abundance of Lactobacillus had fallen while a range of other taxa including Escherichia, Turicibacter and members of Clostridiales increased. This general pattern was followed by all breeds, however, the rate at which succession occured differed as Ross matured quicker than Cobb with Hubbard as an intermediate.